2011
DOI: 10.1007/s00586-011-1759-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the direct repair of spondylolisthesis

Abstract: Direct repair of spondylolisthesis can save a functional segment in young patients with slight slipping. Since 1968 many surgeons have proposed different technical solutions to obtain the isthmic repair. Their results changed according to the technique used, the extent of listhesis and the age of the patient. The aim of our study was to perform a retrospective review on the long-term results of the direct repair of spondylolisthesis, according to the different techniques used. We operated 62 patients for isthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…It was also noted that in some cases, the screw itself occupied much of the space of the defect in the region of the isthmus, which may prevent bony contact with the graft. 13 Screw loosening and screw breakage were the most common complications noted in our study. The complication rate ranged from 0% 21 to 37.5%.…”
Section: 21 3848mentioning
confidence: 53%
See 3 more Smart Citations
“…It was also noted that in some cases, the screw itself occupied much of the space of the defect in the region of the isthmus, which may prevent bony contact with the graft. 13 Screw loosening and screw breakage were the most common complications noted in our study. The complication rate ranged from 0% 21 to 37.5%.…”
Section: 21 3848mentioning
confidence: 53%
“…The series by Giudici et al 13 reported the lowest fusion rate. The authors opined that accurate screw placement was the main technical difficulty to achieve a good purchase and compression at the site of defect.…”
Section: 21 3848mentioning
confidence: 91%
See 2 more Smart Citations
“…are various surgical techniques found in the literature (1,2,8,11). Some suggested good results (17) and some emphasized ineffective results and complications of surgery (5,6,8). In the presented study, the fact is that conservative treatment did not change the fate and all elderly patients over 70 years old underwent surgery.…”
Section: Atabey C Et Al: Degenerative Spondylolisthesis In Elderly Pmentioning
confidence: 64%